Microkeratome versus manually dissected donor tissue for Descemet stripping endothelial keratoplasty: A randomized prospective study - Ritu Mali; Smruti R. Priyadarshini; Srikant K. Sahu; Amrita Mohanty; Sujata Das (Indian Journal of Ophthalmology)
Purpose: To compare the visual outcomes, postoperative complications, and graft asymmetry between precut and manually dissected donor tissues for Descemet stripping automated endothelial keratoplasty (DSAEK) and Descemet stripping endothelial keratoplasty (DSEK) procedures, respectively. Methods: Seventy eyes of 70 patients undergoing DSEK/DSAEK at a tertiary eyecare center in eastern India were included in this prospective randomized control study. The 70 eyes were divided equally into two groups. Group A (n = 35) and Group B (n = 35) underwent DSEK and DSAEK procedures, respectively. the operating surgeons prepared the manually dissected corneal grafts using lamellar dissectors. the eye bank technicians prepared the precut corneal grafts using a microkeratome. The patients were investigated postoperatively after 1 day, 1 week, 1 month, 3 months, and 6 months. The data were compared for visual outcomes [uncorrected visual acuity (UCVA), best-corrected visual acuity (BCVA), spherical and cylindrical refraction, and spherical equivalent], incidence of postoperative complications, and pachymetry. Results: The mean age was 56.5 (±17.8) years, and the male-to-female ratio was 1.3:1. The most common indications were pseudophakic bullous keratopathy (45.71%, 32/70), failed graft (32.86%, 23/70), and Fuchs’ endothelial corneal dystrophy (10%, 7/70). The indications for surgery (P = 0.732) and donor (P = 0.258) and host pachymetry (P = 0.986) were comparable between both groups. There was no significant difference in change of UCVA, BCVA, and postoperative refraction (mean spherical refraction, P = 0.849; mean cylindrical refraction, P = 0.516; spherical equivalent, P = 0.518) between the two groups. Postoperative complications like graft detachment (P = 0.179), graft failure (P = 0.513), graft infiltrate (P = 0.428), and endophthalmitis (P = 0.493) were higher in the DSAEK group; however, the difference between the groups was insignificant. The graft asymmetry index was higher in DSAEK than in DSEK; the difference was significant till the 1-month follow-up (P = 0.005). Conclusion: The outcome was similar in both groups. Therefore, manual donor dissection can be an alternative for microkeratome-assisted dissection in low-resource centers and countries to achieve good results.